Contribution to the knowledge of the Neotropical Uropodina (Acari: Mesostigmata) - Kontschán, Jenő; Ermilov, Sergey G.; Friedrich, Stefan (Zootaxa, 2023)
Two new species of Uropodina are described from Peru—Stammeroplitis panguanaensis sp. nov. and Rotundabaloghia (Circobaloghia) koepckeorum sp. nov.. The genus Stammeroplitis is diagnosed and a key to its Neotropical species is presented. Twenty species of Oplitis are moved to Stammeroplitis. The new family Clausiadinychidae fam. nov. is established for the genus Clausiadinychus and a key to the known species of Clausiadinychus species is provided. New information is presented for three known species of Uropodina (Clausiadinychus quadricaudatus Hirschmann, 1973, Rotundabaloghia dillerae Błoszyk, 2019 and Trichouropoda solaris Hirschmann, 1972).